2019
DOI: 10.12688/f1000research.19236.3
|View full text |Cite
|
Sign up to set email alerts
|

Using singscore to predict mutation status in acute myeloid leukemia from transcriptomic signatures

Abstract: Advances in RNA sequencing (RNA-seq) technologies that measure the transcriptome of biological samples have revolutionised our ability to understand transcriptional regulatory programs that underpin diseases such as cancer. We recently published singscore - a single sample, rank-based gene set scoring method which quantifies how concordant the transcriptional profile of individual samples are relative to specific gene sets of interest. Here we demonstrate the application of singscore to investigate transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…primarily in oral cavity cancers. We have quantified p-EMT using a signature of n = 15 common p-EMT genes defined across patients with oral cavity cancers (Puram et al, 2017) by applying the recently published Single Sample Scoring of Molecular Phenotype (Bhuva et al, 2019; Foroutan et al, 2018), which represents a superior gene set enrichment analysis (GSEA) providing stable Singscores, within the TCGA HNSCC cohort (Cancer Genome Atlas, 2015). Even though not reliant on background samples, Singscores are a GSEA that depends on a sufficiently large number of total genes to quantify enrichment scores for a chosen gene set (n = 15 genes out of a pool of n = 10,000 in the present study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…primarily in oral cavity cancers. We have quantified p-EMT using a signature of n = 15 common p-EMT genes defined across patients with oral cavity cancers (Puram et al, 2017) by applying the recently published Single Sample Scoring of Molecular Phenotype (Bhuva et al, 2019; Foroutan et al, 2018), which represents a superior gene set enrichment analysis (GSEA) providing stable Singscores, within the TCGA HNSCC cohort (Cancer Genome Atlas, 2015). Even though not reliant on background samples, Singscores are a GSEA that depends on a sufficiently large number of total genes to quantify enrichment scores for a chosen gene set (n = 15 genes out of a pool of n = 10,000 in the present study).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, reducing dimensional complexity of p-EMT by Singscoring allowed a distinctive stratification and prognosis of clinical outcome depending on disease sub-groups. Measuring the degree of p-EMT is feasible at the single patient level using Singscores in bulk sequencing information and provides a novel stratification parameter for HNSCC patients in the context of next generation sequencing-based precision medicine (Bhuva et al, 2019). A high p-EMT SING score in patients suffering from oral cavity cancers of the malignant-basal subtype might represent a supportive rationale for full treatment regimens, whereas p-EMT low-risk patients might profit from treatment de-escalation.…”
Section: Discussionmentioning
confidence: 99%
“…Samples with the phrase ‘carcinoma’ in their annotation were considered carcinomas and were used to derive our stable gene list. TCGA breast cancer data were downloaded and processed using an alternate pipeline described in a R/Bioconductor-based workflow ( 26 ). This data was used to assess the impact of processing pipelines on putative stable genes.…”
Section: Methodsmentioning
confidence: 99%
“…Samples with the phrase "carcinoma" in their annotation were considered carcinomas and were used to derive our stable gene list. TCGA breast cancer data were downloaded and processed using an alternate pipeline described in a R/Bioconductor-based workflow (25). This data was used to assess the impact of processing pipelines on putative stable genes.…”
Section: Pre-processing Datasetsmentioning
confidence: 99%
“…We previously developed a method, singscore, to score individual samples against gene set signatures using transcriptomic data and showed that these scores can assist in assessing the molecular phenotype of tissues and cell lines (35). Though the method has been applied in diverse scenarios in an exploratory context (25,35,36,42,43), the potential for clinical translation is limited by a requirement for transcriptome-wide measurements.…”
Section: Computing Transcriptomic Signature Scores Using a Reduced Numentioning
confidence: 99%